Colonización de macroinvertebrados acuáticos en hojarasca de orilla, en quebrada circundante a los ambientes de la Facultad de Ciencias Biológicas – Zungarococha - Malca Flores, Lessy Liceth (2025)
This study was carried out in a stream surrounding the UNAP Faculty of Biological Sciences, located in the district of San Juan Bautista, province of Maynas in the Loreto region, during the months of March - May 2022. The objective was to analyze the colonization of aquatic macroinvertebrates in bank litter. The type of research was quantitative, observational, and longitudinal, with a descriptive design. For data collection, three sections were located along the stream. In each section, on the bank of the stream, three rows of 6 collection bags each were placed on both sides of the stream, making a total of 36, which were removed every 10 days, two from each section. A total of 2,811 individuals were recorded; the richness of aquatic macroinvertebrates consisted of 4 phyla, 6 classes, 12 orders, 16 families, and 24 genera. The richest phyla with two taxonomic classes were Annelida and Mollusca. The most diverse class was Insecta with 5 orders (38%), the class Insecta being the richest at 38%. The genera found with more than 50 individuals were Duguesia, Corbicula, Baetodes, Neoelmis, Microcylloepus, and Chironomus. The abundance of functional groups of aquatic macroinvertebrates shows that scrapers represent 45%, being the predominant group, followed by crawlers with 28%, filter feeders with 17%, graspers with 7%, and burrowers with 3%. Regarding the abundance of functional groups and time of occurrence, scrapers were present from the first 10 days, followed by crawlers, filter feeders, graspers, and burrowers, all coinciding with a low presence within the 60 days. The richness of functional groups and time of occurrence in scrapers totaled 1,255 during the 60 days.